Propozycja klasyfikacji metod szacowania kosztu kapitału własnego - Byrka-Kita, Katarzyna (Cost of Equity Valuation Methods - Proposition of Classificatio, 2007)
The article presents classification of the cost of equity valuation methods. As far as debt is concerned the cost of this source of financing can be directly observed or priced easily. Unfortunately with respect to the equity it is much more complicated mainly because the shareholders' expectations cannot be observed directly. There were many methods developed but the academics are still arguing about them. The classification proposed in the paper may be found controversial because the differences are diminishing but at the same time it may give an incentive to a fruitful debate.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 89-97